A Qualitative Analysis of the Culture of Antibiotic Use for Upper Respiratory Tract Infections Among Patients in Northwest Russia - Cantarero-Arevalo, Lourdes; Nørgaard, Lotte S.; Sporrong, Sofia K.; Jacobsen, Ramune; Almarsdóttir, Anna Birna; Hansen, Johanne M.; Titkov, Dmitry; Rachina, Svetlana; Panfilova, Ekaterina; Merkulova, Viktoria; Eseva, Olga; Riabkova, Nadezhda; et al. (Frontiers in Pharmacology, 2022)
Introduction: Due to the globally persistent threat of Antimicrobial Resistance (AMR), the purpose of this study was to gain an in-depth understanding of the antibiotic (AB) practices, knowledge and attitudes among patients residing in five regions in the northwest part of Russia. Given the high prevalence, this study focused on ABs for Upper Respiratory Tract Infections (URTI). Methods: The qualitative, semi-structured interviews followed a guide organized by major themes such as common symptoms, consultations with doctors and external influences in decision-making. Patient participants were recruited via convenience sampling. Fifty-five interviews were conducted among patients using ABs for URTIs purchased with or without prescription. Data was analyzed using a direct content analysis and validation rounds were conducted between interviewers and data analyzers. Results: Self-medication with ABs seemed a common practice across all five Russian regions; in some cases, patients tried to persuade pharmacists into selling them ABs without prescription. Factors, such as time spent going to the doctor, need of a sick leave or self-persuasion, influenced the decisions of whether or not to seek the doctor for symptoms of URTIs. Knowledge of ABs and AMR was generally low; however, some patients with seemingly good knowledge practiced self-medication from time to time. Family members and friends were often involved in decisions about how to handle symptoms of URTIs, especially among those patients using ABs without prescription. Few patients had noticed ABs awareness campaigns, and very few reported having learned something important from them. Conclusions: Despite enforced regulation of AB use in Russia, self-medication still exists. Knowledge is not always linked to appropriate use of AB, and the few campaigns conducted were not always noticed.